Hollow particles and method for producing same

By using an aluminum-containing silica shell in the hollow particles and optimizing the distribution of aluminum and sodium, as well as the hollow rate and shell thickness, the problem of insufficient dielectric characteristics of existing hollow particles is solved, and better dielectric properties and strength are achieved.

CN119836400APending Publication Date: 2025-04-15SETOLAS HLDG INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380038944.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-09
Filing Date
2023-05-02
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing hollow particles are difficult to meet the dielectric characteristics of high-speed and large-capacity in information and communication equipment.

Method used

Using hollow particles in a silica shell containing aluminum, the amount of aluminum gradually decreases from the inside to the outside of the shell, and sodium is added to the shell, and the hollow rate and thickness of the shell are optimized within a certain range.

Benefits of technology

The dielectric properties of hollow particles are significantly improved, including optimization of dielectric constant and dielectric loss tangent, and the intensity and hollow rate of the particles are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836400A_ABST
    Figure CN119836400A_ABST
Patent Text Reader

Abstract

Provided are hollow particles having excellent dielectric properties. A hollow particle according to an embodiment of the present invention has a shell having a hollow interior. And the shell is silicon dioxide containing aluminum. The amount of aluminum present in the first region is greater than the amount of aluminum present in the second region. The first portion is located on the inner side of the shell in the thickness direction of the shell. The second portion is located on the outer side of the shell in the thickness direction of the shell compared with the first portion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to hollow particles having a shell with a hollow interior and a method for producing the same. Prior art

[0002] For example, in the field of information communication equipment, in order to cope with communication in high frequency bands, it is required to make electronic components such as circuit substrates (representatively resin components) have low dielectric constants and low dielectric loss tangents. In order to achieve this requirement, for example, it is proposed that the components contain air with a relatively low dielectric constant. Specifically, according to what is disclosed in Patent Documents 1 and 2, it is proposed to use hollow particles to introduce air. Prior art literature

[0003] Patent Literature Patent Document 1: International Publication No. 2021 / 171858 Patent Document 2: International Publication No. 2021 / 171859 Summary of the invention Problems to be solved by the invention

[0004] In recent years, due to the increase in speed and capacity of information and communication equipment, hollow particles are required to have further improved dielectric properties.

[0005] The present invention has been made to solve the above-mentioned problems, and one of its objects is to provide hollow particles having further improved dielectric properties. Means of solving problems

[0006] (1) The hollow particles disclosed in the present invention have a shell with a hollow interior. The shell is silicon dioxide containing aluminum. The aluminum is present in a greater amount in the first portion than in the second portion. The first portion is located on the inner side of the shell in the thickness direction of the shell. The second portion is located on the outer side of the shell in the thickness direction of the shell compared to the first portion.

[0007] (2) Hollow particles of the present disclosure In the hollow particles described in (1) above, the content of the aluminum is less than 1% of the components constituting the shell.

[0008] (3) Hollow particles of the present disclosure In the hollow particles described in (1) or (2) above, the amount of the aluminum gradually decreases from the inside to the outside of the shell.

[0009] (4) In the hollow particles of the present disclosure, in any one of the hollow particles described in (1) to (3), the oil absorption of the epoxy resin is less than 0.6 g / m 2 .

[0010] (5) The hollow particles of the present disclosure are the hollow particles according to any one of (1) to (4) above, wherein the shell further contains sodium. The content of the sodium in the shell is 3000 ppm or less.

[0011] (6) Hollow particles of the present disclosure In the hollow particles described in any one of (1) to (5) above, the silicon dioxide is amorphous silicon dioxide.

[0012] (7) The hollow particles of the present disclosure are the hollow particles according to any one of (1) to (6) above, wherein the hollow ratio of the shell is 30% to 95%.

[0013] (8) The hollow particles of the present disclosure are the hollow particles according to any one of (1) to (7) above, wherein the shell has a thickness of 25 nm to 500 nm.

[0014] (9) The method for producing hollow particles disclosed in the present invention is the method for producing hollow particles described in any one of (1) to (8) above. The method comprises the steps of: coating a core particle with a shell-forming material to obtain a core-shell particle, removing the core particle from the core-shell particle to obtain a hollow particle precursor, and coating the hollow particle precursor with a shell-forming material.

[0015] (10) Method for producing hollow particles of the present disclosure In the method for producing hollow particles described in (9) above, the core particles contain an alunite-type compound represented by the following general formula (I). M a [Al 1-x M' x ]3(SO4 2- ) y (OH) z ·mH2O……(I) In formula (I), M is selected from Na + , K + NH4 + and H3O + In formula (I), M' is selected from Cu 2+ 、Zn 2+ 、Ni 2+ Sn 4+ 、Zr 4+ and Ti 4+ At least one cation in the formula (I). In the formula (I), a satisfies 0.8≤a≤1.35. In the formula (I), m satisfies 0≤m≤5. In the formula (I), x satisfies 0≤x≤0.4. In the formula (I), y satisfies 1.7≤y≤2.5. In the formula (I), z satisfies 4≤z≤7. Effects of the Invention

[0016] According to the embodiments of the present invention, excellent dielectric characteristics can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic diagram of the long diameter and short diameter. Figure 2 This is a cross-sectional view schematically showing a hollow particle according to one embodiment of the present invention. Figure 3A This is a schematic diagram showing an example of the change in the Al content in the thickness direction of the shell. Figure 3B This is a schematic diagram showing another example of the change in the Al content in the shell thickness direction. Figure 3C This is a schematic diagram showing still another example of the change in the Al content in the shell thickness direction. Figure 4 This is a schematic cross-sectional view of a laminate according to one embodiment of the present invention. Figure 5A This is a TEM observation photograph of the hollow particles of Example 1. Figure 5B This is a TEM observation photograph of the hollow particles of Example 2. Figure 5C This is a TEM observation photograph of the hollow particles of Example 3. Figure 6 This is a cross-sectional SEM observation photograph of the resin molded body of Example 1. DETAILED DESCRIPTION

[0018] Embodiments of the present invention will be described below, but the present invention is not limited to these embodiments.

[0019] (Definition of terms) The definitions of terms in this specification are as follows. 1. The long diameter of the particle The major diameter of the particle is a value measured by a scanning electron microscope (SEM). Figure 1 The major diameter of a particle is the average of the major diameters of randomly selected primary particles, as shown in L. In addition, the primary particle refers to the smallest particle observed by SEM, and is distinguished from aggregated secondary particles. 2. The short diameter of the particle The minor diameter of the particle is a value measured by SEM observation. Figure 1 The short diameter of the particle shown in T is the average of the short diameters of randomly selected primary particles. 3. Aspect Ratio The aspect ratio is a value calculated by dividing the major axis of the particle by the minor axis of the particle.

[0020] A. Hollow particles The hollow particles of one embodiment of the present invention have a shell with a hollow interior. In other words, the hollow particles have a shell and a space surrounded by the shell. The shell contains silicon dioxide. The silicon dioxide is typically amorphous silicon dioxide. The content of silicon dioxide in the shell is, for example, 95% by weight or more, preferably 97% by weight or more, and more preferably 98% by weight or more.

[0021] The shell of the above-mentioned hollow particles contains aluminum (Al). By containing Al, hollow particles with excellent strength (destructive strength) can be obtained. The content of Al is preferably 0.1% or more, more preferably 0.2% or more. On the other hand, by containing Al, the hollow particles have a tendency to increase the dielectric constant and dielectric loss tangent. Therefore, the content of Al is preferably less than 1%, more preferably less than 0.9%, further preferably less than 0.7%, and particularly preferably less than 0.5%. According to such a content, the hollow particles can have extremely excellent dielectric properties. The content of Al can be obtained, for example, by composition analysis using high-frequency inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0022] Hollow particles are formed in such a way that the amount of Al in the inner side of the shell in the thickness direction is more than the outer side in the thickness direction. According to this method, hollow particles with excellent strength (destructive strength), hollow ratio, and dielectric properties can be obtained. Specifically, the region where there are more Al in the hollow particles is easily softened during firing. That is, the hollow particles can make the firing temperature low in the manufacturing process. In addition, by having more Al in the region, the hollow particles can be further shrunk by firing on the inner side compared with the outer side of the hollow particle precursor constituting the shell. Hollow particles can improve the destructive strength by having more Al in the region. It can be considered that for hollow particles, the particle size is maintained by suppressing the softening and shrinkage of the outer side in the shell, and the internal space is expanded by the softening and shrinkage of the inner side in the shell, which helps to improve the hollow ratio. In other words, for hollow particles, the shell strength and hollow ratio can be improved by the different distribution of the amount of Al in the outer and inner sides of the shell. The excellent strength of the hollow particles and the low dielectric constant, for example, when making a resin composition containing resin and hollow particles, can effectively prevent the hollow particles from being destroyed. As a result, the hollow state of the particles can be maintained, which is extremely helpful for improving dielectric properties. It should be noted that in hollow particles, if the thickness of the shell is thin, Al is easily evenly distributed. For example, when Al is evenly distributed, the inner and outer sides of the hollow particles have a tendency to shrink in the same manner as the shell, and the particle size becomes smaller.

[0023] Figure 2 FIG. 1 is a cross-sectional view schematically showing a hollow particle according to an embodiment of the present invention. Figure 2In the figure, the cross section of the hollow particle is not hatched for convenience. The hollow particle 2 has a shell 4 and a space (hollow portion) 6 surrounded by the shell 4. In the shell 4, the amount of Al in the first portion 4a located on the inner side in the thickness direction is greater than the amount of Al in the second portion 4b located on the outer side in the thickness direction relative to the first portion 4a. For example, in the case of Figure 2 As shown, the first part 4a of the hollow particle is located on the surface or near the surface of the inner side of the shell 4, and the second part 4b is located on the surface or near the surface of the outer side of the shell. In this case, the Al content of the first part 4a is preferably more than 2 times the Al content of the second part 4b, and more preferably more than 3 times. The distribution of the Al content can be obtained by, for example, performing composition analysis using an energy dispersive X-ray spectrometer (TEM-EDS) using a transmission electron microscope (TEM). In one embodiment, the Al content can be evaluated by the molar ratio of Al to Si.

[0024] As an example of the distribution of the amount of Al in the thickness direction, there can be cited a form in which the amount of Al decreases continuously from the inside to the outside of the shell. In this case, the manner in which the amount of Al changes is not particularly limited. For example, Figure 3A As shown, the amount of Al present can decrease linearly with respect to the distance from the inner surface of the shell. Figure 3B As shown, the Al content can be reduced exponentially relative to the distance from the inner surface of the shell. Specifically, the Al content of the hollow particles can be controlled by controlling the addition method of the Al raw material during the first silica treatment of the core particles and the second silica treatment of the hollow particle precursor. For hollow particles, when the Al content decreases linearly, there is a tendency for the hollow rate to be higher than that of Al being uniformly distributed in the shell. For hollow particles, when the Al content decreases exponentially, there is a tendency for the hollow rate to be higher than that of linear reduction.

[0025] As another example of the distribution of the Al content in the thickness direction, there can be cited a form in which the Al content decreases stepwise from the inside to the outside of the shell. In other words, the Al content of the hollow particle decreases discontinuously from the inside to the outside of the shell. For example, a hollow particle such as Figure 3C As shown, the following form can be given: there is a first region 41 with a constant Al content from the inner surface of the shell to the outer side, and there is a second region 42 with a smaller Al content than the first region 41 outside the first region 41. Figure 3C In the figure, for convenience, the first region 41 and the second region 42 are represented by straight lines, but the constant Al content means, for example, that the difference in the Al content is 20% or less. Figure 3CIn the example in which the Al content is reduced in two stages, the Al content may be reduced in three or more stages. When the Al content of the hollow particles is reduced in stages, the effect of improving the strength and the hollowness can be enhanced.

[0026] The shell of the hollow particle may contain sodium (Na). If the content of Na in the hollow particle is too much, it is difficult to increase the firing temperature in the manufacturing process of the hollow particle, and there is a tendency to shrink. The content of Na is preferably less than 3000ppm, more preferably less than 2000ppm, and further preferably less than 1500ppm. On the other hand, the content of Na is preferably more than 100ppm. The content of Na can be obtained by, for example, atomic absorption spectroscopy (AAS) for composition analysis.

[0027] In the hollow particles, the amount of Na present is preferably more on the inside of the shell in the thickness direction than on the outside in the thickness direction. It is believed that in the hollow particles, if a portion of Si (4 +) is replaced by Al (3 +), Na easily enters to fill the electron deficiency. Therefore, it is believed that the hollow particles have a tendency to have more Na in the region where there is more Al.

[0028] In one embodiment, the primary particles of the hollow particles preferably satisfy 1≤D SL ≤1.5. By making the primary particles of the hollow particles satisfy 1≤D SL ≤1.5, the deviation between particles can be suppressed and the dielectric properties can be made uniform. The primary particles of the hollow particles more preferably satisfy 1≤D SL ≤1.4, preferably 1≤D SL ≤1.3. Here, D SL Yes D 75L / D 25L , D 25L and D 75L They respectively show the 25th and 75th values ​​when the major axes of 100 randomly selected primary particles are measured in observation using a scanning electron microscope and the major axes are arranged in order from the smallest to the largest.

[0029] The primary particles of the hollow particles preferably satisfy 1≤D ST ≤1.5, preferably 1≤D ST ≤1.4, preferably 1≤D ST ≤1.3. Here, D ST Yes D 75T / D 25T , D 25T and D 75T They respectively show the 25th and 75th values ​​when the minor axes of 100 randomly selected primary particles are measured in observation using a scanning electron microscope and the particles are arranged in order from the smallest to the largest.

[0030] The aspect ratio of the hollow particles is preferably less than 2, more preferably 1.9 or less. On the other hand, the aspect ratio of the hollow particles is 1 or more, preferably greater than 1, more preferably 1.1 or more.

[0031] The hollow particles may have any appropriate shape. Examples of the shape of the hollow particles include: elliptical, spherical, agglomerated, scaly, plate-like, film-like, cylindrical, prism-like, flat, go-shaped, and rice-shaped. As the shape of the hollow particles, preferably, a spherical or go-shaped shape may be used. By using such a shape, for example, the above-mentioned D can be well satisfied. SL and D ST .

[0032] The major diameter of the hollow particles is preferably 0.5 μm or more, more preferably 1 μm or more. The reason is that if the major diameter of the hollow particles is, for example, 0.5 μm or more, the hollow ratio described below can be fully satisfied. On the other hand, the major diameter of the hollow particles is preferably 10 μm or less, more preferably 5 μm or less. The reason is that if the major diameter of the hollow particles is, for example, 10 μm or less, it is extremely helpful for miniaturization or filmization of the components used.

[0033] The short diameter of the hollow particles is preferably 0.25 μm or more, more preferably 0.5 μm or more. The reason is that if the short diameter of the hollow particles is, for example, 0.25 μm or more, the following hollow ratio can be fully satisfied. On the other hand, the short diameter of the hollow particles is preferably 10 μm or less, more preferably 5 μm or less. The reason is that if the short diameter of the hollow particles is, for example, 10 μm or less, it is extremely helpful for miniaturization or filmization of the components used.

[0034] The thickness of the shell of hollow particles is preferably more than 25nm, more preferably more than 50nm, and more preferably more than 75nm. According to such thickness, for example, when making resin composition, it is possible to effectively prevent the hollow particles from being destroyed. On the other hand, the thickness of the shell of hollow particles is preferably less than 500nm, more preferably less than 350nm, and more preferably less than 250nm. According to such thickness, it is possible to fully meet the hollow ratio described later, which is extremely helpful for the improvement and lightweight of dielectric properties. It is explained that the thickness of the shell can be measured by TEM observation. For example, it is obtained in the following manner: measure the thickness of the shell of the randomly selected hollow particles, and calculate the average value of the thickness of the measured shell. The thickness of the shell of the hollow particles sometimes affects the distribution of the Al content.

[0035] The hollow ratio of the hollow particles is preferably 30% or more, more preferably 40% or more, further preferably 45% or more, and particularly preferably 50% or more. According to such a hollow ratio, for example, it is extremely helpful to improve and lighten the dielectric properties. On the other hand, the hollow ratio of the hollow particles is preferably 95% or less, more preferably 90% or less, further preferably 85% or less, and particularly preferably 80% or less. According to such a hollow ratio, for example, when making a resin composition, the hollow particles can be effectively prevented from being destroyed. It should be noted that the hollow ratio can be calculated based on the above-mentioned major diameter and minor diameter and the thickness of the above-mentioned shell.

[0036] The BET specific surface area of ​​the hollow particles is preferably 30 m 2 / g or less, more preferably 20m 2 / g or less, more preferably 10m 2 On the other hand, the BET specific surface area of ​​the hollow particles is, for example, 0.5 m 2 / g or more, can also be 1m 2 / g or above.

[0037] The diameter of hollow particles is 1nm to 100nm of the micropore cumulative micropore volume is preferably below 0.1cc / g, more preferably below 0.08cc / g, further preferably below 0.06cc / g. According to such micropore volume, for example, in resin combination, it is possible to effectively prevent resin from penetrating into the hollow particle interior, extremely contributing to the raising of dielectric properties. On the other hand, the diameter of hollow particles is 1nm to 100nm of the micropore cumulative micropore volume, for example, more than 0.01cc / g.

[0038] The diameter of hollow particle is 1nm to 10nm micropore cumulative micropore volume is preferably below 0.025cc / g, more preferably below 0.020cc / g, further preferably below 0.010cc / g.According to such micropore volume, for example, in resin combination, it is possible to effectively prevent resin from penetrating into hollow particle inside, extremely contribute to the raising of dielectric properties.On the other hand, the diameter of hollow particle is 1nm to 10nm micropore cumulative micropore volume is for example more than 0.001cc / g.

[0039] The density of the hollow particles is preferably 0.90 g / cc or less, more preferably 0.80 g / cc or less. On the other hand, the density of the hollow particles is preferably 0.55 g / cc or more, more preferably 0.60 g / cc or more. With such a density, the hollow particles can achieve the strength and hollowness of the shell.

[0040] The dielectric constant of the hollow particles at 25°C and 10 GHz is preferably 2.2 or less, more preferably 2.0 or less. On the other hand, the dielectric constant of the hollow particles at 25°C and 10 GHz is, for example, 1.0 or more. The dielectric loss tangent of the hollow particles at 25°C and 10 GHz is preferably 0.005 or less, more preferably 0.002 or less. On the other hand, the dielectric loss tangent of the hollow particles at 25°C and 10 GHz is, for example, 0.0001 or more.

[0041] The destructive strength of hollow particles is preferably more than 10MPa, more preferably more than 12MPa, further preferably more than 14MPa, particularly preferably more than 16MPa. According to such destructive strength, for example, when making resin combination, hollow particles can be effectively prevented from being destroyed. As a result, the hollow state of particles can be kept, which greatly contributes to the raising of dielectric properties. On the other hand, the destructive strength of hollow particles is, for example, below 800MPa.

[0042] The destructive strength of the hollow particles can be measured, for example, by a micro compression tester ("MCT-510" manufactured by Shimadzu Corporation) using a length measuring kit and a side observation kit. Specifically, it can be measured by spreading a very small amount of hollow particles on the lower pressure plate and performing a destructive test on each particle under the following measurement conditions. ■Test force: 0.980mN ■Load speed: 0.0223mN / sec ■Upper pressure head: Flat surface φ20μm

[0043] For example, 10 particles are measured, and the breaking strength Cs is calculated from the particle size d (mm) of each particle and the test force P (N) at the breaking point. In the calculation of the breaking strength Cs, the following formula of JIS R 1639-5 "Determination of properties of precision ceramic particles - Part 5: Single particle crushing strength" is used. Cs=2.48P / πd 2 The breaking strength of the hollow particles can be obtained by calculating the average breaking strength Cs (MPa) of 10 particles.

[0044] The oil absorption of the epoxy resin per 1g of the hollow particles is preferably 2.3g or less, more preferably 2.0g or less. In addition, the oil absorption of the epoxy resin of the hollow particles is preferably less than 0.6g / m 2 , more preferably 0.46 g / m 2 Below, more preferably 0.35g / m 2 the following.

[0045] In one embodiment, the hollow particles are preferably surface treated with any appropriate surface treatment agent. As the surface treatment agent, for example, at least one selected from higher fatty acids, anionic surfactants, cationic surfactants, phosphates, coupling agents, esters of polyols and fatty acids, acrylic polymers, and silicone treatment agents can be used.

[0046] As the method for producing the above-mentioned hollow particles, any appropriate method can be adopted. The method for producing hollow particles according to one embodiment of the present invention includes the following steps: covering the core particles with a shell-forming material to obtain core-shell particles; removing the core particles from the core-shell particles to obtain a hollow particle precursor; and covering the hollow particle precursor with a shell-forming material. By covering the hollow particle precursor with a shell-forming material, for example, the reduction in hollowness can be suppressed, and a strong shell can be formed. Specifically, the hollow particle precursor obtained by removing the core particles may have micropores and may be in a relatively brittle state. By filling the micropores of the hollow particle precursor with a shell-forming material, the hollow particle precursor can be prevented from shrinking, and hollow particles with a strong shell can be obtained. The shrinkage of the hollow particle precursor refers to softening shrinkage, for example.

[0047] The primary particles of the core particles preferably satisfy 1≤D SL ≤1.5, more preferably 1≤D SL ≤1.4, more preferably 1≤D SL ≤1.3. In addition, the primary particles of the core particles preferably satisfy 1≤D ST ≤1.5, more preferably 1≤D ST ≤1.4, more preferably 1≤D ST ≤1.3. SL and D ST , as described above.

[0048] The aspect ratio of the core particle is preferably less than 2, more preferably less than 1.9. On the other hand, the aspect ratio of the core particle is greater than 1, preferably greater than 1, more preferably greater than 1.1. As the shape of the core particle, for example, elliptical, spherical, agglomerated, scaly, plate-like, film-like, cylindrical, prism-like, flat, go-shaped, rice-shaped. As the shape of the core particle, preferably a spherical or go-shaped shape can be used.

[0049] The major diameter of the core particle is preferably 0.5 μm or more, more preferably 1 μm or more. On the other hand, the major diameter of the core particle is preferably 10 μm or less, more preferably 5 μm or less. The minor diameter of the core particle is preferably 0.25 μm or more, more preferably 0.5 μm or more. On the other hand, the minor diameter of the core particle is preferably 10 μm or less, more preferably 5 μm or less.

[0050] Any suitable material can be used as the material for forming the core particles. For example, an aluminum-containing material can be used to satisfy the distribution of the above-mentioned Al content in the obtained hollow particles. In one embodiment, the core particles are preferably formed of an alunite-type compound represented by the following general formula (I). M a [Al 1-x M' x ]3(SO4 2- ) y (OH) z ·mH2O…(I) In formula (I), M is selected from Na + , K + NH4 + and H3O + In formula (I), M' is selected from Cu 2+ 、Zn 2+ 、Ni 2+ Sn 4+ 、Zr 4+ and Ti 4+ At least one cation in the formula (I). In the formula (I), a satisfies 0.8≤a≤1.35. In the formula (I), m satisfies 0≤m≤5. In the formula (I), x satisfies 0≤x≤0.4. In the formula (I), y satisfies 1.7≤y≤2.5. In the formula (I), z satisfies 4≤z≤7.

[0051] As the above-mentioned shell-forming material, for example, sodium silicate (Na2O·nSiO2) and alkoxysilane represented by tetraethoxysilane (Si(OCH2CH3)4) can be used. In one embodiment, sodium silicate (water glass) is used. Due to the presence of Na, for example, it is easy to soften in the calcination described later and the calcination temperature is easy to control. The shell-forming material may contain Al. For example, in the case where the core particles are covered with the shell-forming material multiple times, the Al concentration in the shell-forming material used for each treatment can be adjusted to satisfy the distribution of the above-mentioned Al content in the obtained hollow particles.

[0052] The amount of coating of the shell-forming material can be adjusted by any appropriate method. For example, the amount of coating can be adjusted by controlling the pH value when coating with a shell-forming material containing sodium silicate. Specifically, sodium silicate is stable in a high pH region. For example, sodium silicate is stable above pH 11. Therefore, by lowering the pH value, the sodium silicate molecules can be condensed, and silicon dioxide can be effectively precipitated on the core particles. Here, in the case where the core particles contain the above-mentioned alunite-type compound, the water slurry of the alunite-type compound itself can show acidity. The acidity of the water slurry of the alunite-type compound itself is, for example, pH 3 to 5. Since the water slurry of the alunite-type compound itself is acidic, for example, even without using a pH adjuster for lowering the pH value, silicon dioxide can be effectively precipitated on the core particles. In the case where the core particles containing the alunite-type compound are coated with a shell-forming material containing sodium silicate multiple times, a pH adjuster can be used in more than one of the multiple times. In this case, as a pH adjuster, for example, an acidic solution such as hydrochloric acid or sulfuric acid can be used. By using an acidic solution, hollow particles having a low Na content can be obtained.

[0053] It should be noted that by heating when covering with a shell-forming material, the covering of the shell-forming material can be promoted. Specifically, the precipitation of the shell can be promoted and the speed of shell formation can be increased. The heating temperature when covering with a shell-forming material is, for example, 80°C to 90°C. In addition, the covering amount can be adjusted by controlling the concentration and the amount of the shell-forming material when covering. In the case of covering the core particles with a shell-forming material containing sodium silicate, the concentration of sodium silicate in the shell-forming material is, for example, 0.1 mol / L to 2 mol / L.

[0054] The removal of the core particles is typically performed by dissolving the core particles in an acidic solution. As the acidic solution, for example, hydrochloric acid, sulfuric acid, and nitric acid can be used. The dissolution temperature is, for example, 30°C to 90°C, preferably 50°C to 80°C. According to such a temperature, it is possible to suppress undesirable conditions such as easy damage to the shell, and effectively dissolve the core particles. In one embodiment, sulfuric acid is used as the acidic solution, for example, from the viewpoint of reusing the substance obtained by reacting with the core particles. As the substance obtained by reacting with the core particles, for example, salts can be cited. The concentration of sulfuric acid is, for example, 0.1 mol / L to 3.5 mol / L, preferably 0.5 mol / L or more. When dissolving the core particles containing an alunite-type compound, the Al content can be well achieved, for example, by adjusting the acidic solution, the temperature and time of the dissolution.

[0055] The method for manufacturing the hollow particles may include calcining the core-shell particles before removing the core particles. In the case where the core particles contain the alunite-type compound, it is preferred to calcine before removing the core particles. Calcination is preferably performed under an atmospheric atmosphere, for example. The reason is that since the alunite-type compound may have acid resistance, the alunite-type compound changes by calcination, and the core particles after calcination become a state that is easily dissolved in an acidic solution. Specifically, the part with low agglomeration density of the core particles containing the alunite-type compound is easily dissolved in an acidic solution, but the part with high agglomeration density is difficult to dissolve in an acidic solution, and the amount of dissolution in the acidic solution, for example, stays at about 30% by weight. By calcining, aluminum oxide (Al2O3) that is easily dissolved in an acidic solution can be generated from the alunite-type compound, thereby improving the solubility of the core particles in an acidic solution.

[0056] The calcination temperature of the core-shell particles is, for example, 300°C to 900°C, preferably 300°C to 650°C. According to such a calcination temperature, the crystallization of the shell can be suppressed to generate the above-mentioned aluminum oxide. The calcination time is, for example, 0.5 hours to 20 hours. Calcination can be carried out continuously or in multiple stages at different temperatures. It should be noted that when calcination is carried out in multiple stages, the above-mentioned calcination time is the sum of the calcination times of each stage. In one embodiment, the calcination temperature of the core-shell particles can be adjusted to satisfy the distribution of the above-mentioned Al content in the obtained hollow particles.

[0057] The shell-forming material for covering the hollow particle precursor is preferably selected in accordance with the shell-forming material for covering the core particle. Specifically, when sodium silicate is used as the shell-forming material for covering the core particle, sodium silicate is preferably used as the shell-forming material for covering the hollow particle precursor.

[0058] When the hollow particle precursor is covered with a shell-forming material containing sodium silicate, it is preferred to adjust the covering amount by controlling the pH value. Specifically, sodium silicate is stable in a high pH region. A high pH region refers to, for example, a pH value of 11 or more. Regarding sodium silicate, it is preferred that, for example, the pH value is lowered by using a pH adjusting agent to condense the sodium silicate molecules and effectively precipitate silicon dioxide on the hollow particle precursor. As a pH adjusting agent, for example, an acidic solution such as hydrochloric acid or sulfuric acid can be used.

[0059] The manufacturing method of the above-mentioned hollow particles may include calcining a hollow particle precursor covered by a shell forming material. Specifically, the calcination of the hollow particle precursor can be carried out after the hollow particle precursor is covered with a shell forming material. By calcining the hollow particle precursor, it is possible to obtain hollow particles that are extremely helpful in improving dielectric properties. Specifically, the hydrophobicity of the hollow particle precursor surface can be improved. More specifically, the silanol group on the surface of the hollow particle precursor can be changed into siloxane. In addition, it is possible to obtain hollow particles that are easily matched or dispersed in the resin when making a resin composition. Specifically, by calcining, it is appropriately shrunk, thereby preventing the fusion of particles to each other, and filling the micropores on the surface of the hollow particle precursor to obtain a hollow particle with a smooth surface. By obtaining a hollow particle with a smooth surface, for example, the above-mentioned BET specific surface area and micropore volume can be well achieved. In one embodiment, the distribution of the above-mentioned Al presence amount can be satisfied in the obtained hollow particles by adjusting the calcination temperature of the hollow particle precursor.

[0060] The calcination temperature of the hollow particle precursor is, for example, 300°C to 1300°C, preferably 700°C to 1300°C, and more preferably 900°C to 1300°C. According to such a calcination temperature, the above-mentioned hydrophobization can be well achieved. In addition, calcination at such a calcination temperature can achieve a higher hollowness. Specifically, by calcining the hollow particle precursor in the state of filling the above-mentioned micropores with the covering of the shell forming material, the shrinkage of the hollow particle precursor can be suppressed, and hydrophobization can be well achieved. The calcination time of the hollow particle precursor is, for example, 0.1 hour to 10 hours. Calcination can be carried out continuously or in multiple stages at different temperatures. For example, it can be calcined at a temperature T1 lower than 950°C, and then calcined at a temperature T2 above 950°C. At this time, the difference (T2-T1) between the temperature T1 and the temperature T2 is preferably 150°C or more, more preferably 250°C or more. In addition, when sintering is performed in multiple stages, the above-mentioned sintering time is the total of the sintering time of each stage.

[0061] The manufacture method of the above-mentioned hollow particle can include before the calcination of the above-mentioned hollow particle precursor, acid treatment is implemented to the hollow particle precursor. Acid treatment is preferably carried out using acidic solutions such as hydrochloric acid and sulfuric acid representatively. When sodium silicate is used as the shell forming material, the hollow particle precursor can contain Na. By utilizing acid treatment to remove Na, the calcination temperature of the hollow particle precursor can be set higher, thereby being able to obtain extremely helpful hollow particles improving dielectric properties.

[0062] The method for producing the hollow particles is preferably such that the process of obtaining the core-shell particles includes a drying treatment. Specifically, it is preferred that when the core particles are covered with a shell-forming material multiple times, the core particles covered with the shell-forming material are dried, and then the shell-forming material is used again to cover the core particles. The drying temperature in the process of obtaining the core-shell particles is, for example, 90°C to 120°C. The drying time in the process of obtaining the core-shell particles is, for example, 3 hours to 24 hours. By including such a drying treatment, for example, regardless of whether a pH adjuster is used when covering with a shell-forming material, the above-mentioned oil absorption can be well achieved.

[0063] In one embodiment of the present invention, the hollow particles are used as a function-imparting agent for a resin material. Hereinafter, a resin composition containing the hollow particles will be described.

[0064] B. Resin composition The resin composition of one embodiment of the present invention contains a resin and the hollow particles. In the resin composition, the hollow particles can well maintain their hollow state. In addition, in a resin molded body molded using the resin composition, the hollow particles can well maintain their hollow state.

[0065] The above-mentioned resin can be selected according to the purpose of the obtained resin composition, for example, any appropriate resin. For example, the resin can be a thermoplastic resin or a thermosetting resin. As specific examples of the resin, epoxy resin, polyimide resin, polyamide resin, polyamide-imide resin, polyetheretherketone resin, polyester resin, polyhydroxy polyether resin, polyolefin resin, fluororesin, liquid crystal polymer, modified polyimide can be mentioned. They can be used alone or in combination of two or more.

[0066] The content of the hollow particles in the resin composition is preferably 0.1% by weight or more, more preferably 0.5% by weight or more, while the content is preferably 90% by weight or less, more preferably 85% by weight or less.

[0067] The resin composition preferably contains 0.5 parts by weight or more, more preferably 1 part by weight or more of hollow particles per 100 parts by weight of the resin, and preferably contains 300 parts by weight or less, more preferably 200 parts by weight or less of hollow particles per 100 parts by weight of the resin.

[0068] The volume ratio of the hollow particles in the resin composition is preferably 0.1% or more, more preferably 0.5% or more. On the other hand, the volume ratio of the hollow particles in the resin composition is preferably 70% or less, more preferably 60% or less. The reason is, for example, that the processability when making the resin composition can be excellent.

[0069] The hollow ratio of the hollow particles in the resin composition is preferably 30% or more, more preferably 40% or more, further preferably 45% or more, particularly preferably 50% or more.

[0070] The above-mentioned resin composition may contain any component. As any component, for example, there can be mentioned: a curing agent, a stress reducing agent, a coloring agent, a close contact improving agent, a mold release agent, a flow regulator, a defoaming agent, a solvent, and a filler. They can be used alone or in combination of two or more. In one embodiment, the resin composition contains a curing agent. Relative to 100 parts by weight of the resin, the content of the curing agent is, for example, 1 part by weight to 150 parts by weight.

[0071] As the preparation method of the above-mentioned resin combination, any appropriate method can be adopted. Specifically, by any appropriate dispersion method, the above-mentioned hollow particles are dispersed in the above-mentioned resin, thereby obtaining the resin combination. As the dispersion method, for example, the dispersion using various agitators such as a homogenizer, a dispersing machine, a ball mill, the dispersion using a rotation and revolution agitator, the dispersion using the shear force of three rollers, and the dispersion using ultrasonic treatment can be cited.

[0072] The above-mentioned resin composition can be made into a resin molded body formed into a desired shape representatively. For example, it can be made into a resin molded body formed into a desired shape using a mold. When the resin molded body is formed, the resin composition can be subjected to any appropriate treatment. For example, the resin composition can be subjected to a curing treatment.

[0073] In one embodiment of the present invention, the resin composition may be used as a resin layer included in a laminate. Hereinafter, a laminate having a resin layer formed of the resin composition will be described.

[0074] C. Laminate Figure 41 is a schematic cross-sectional view of a laminate according to an embodiment of the present invention. The laminate 10 has a resin layer 11 and a metal foil 12. The resin layer 11 is formed from the above-mentioned resin composition. Specifically, the resin layer 11 contains the above-mentioned resin and the above-mentioned hollow particles. Although not shown in the figure, the laminate 10 may contain other layers. As other layers, for example, a substrate may be cited. The substrate may be laminated on one side of the resin layer 11. Specifically, the substrate may be arranged on the side of the resin layer 11 where the metal foil 12 is not arranged. As the substrate, a resin film may be used representatively. Different from the illustrated example, the laminate 10 may be configured to have a metal foil 12 arranged on the surface of a laminate structure containing a plurality of resin layers 11. The laminate 10 may also be configured to have a metal foil 12 arranged on both sides of a laminate structure containing a plurality of resin layers 11. In addition, the laminate 10 may also be configured to have a structure in which a combination of the resin layer 11 and the metal foil 12 is overlapped multiple times. The laminate 10 may be used representatively as a wiring circuit substrate. The metal foil 12 is formed into a predetermined shape so as to constitute a predetermined circuit wiring, for example.

[0075] The thickness of the resin layer is, for example, 5 μm or more, preferably 10 μm or more. On the other hand, the thickness of the resin layer is, for example, 100 μm or less, preferably 50 μm or less, and more preferably 25 μm or less. Such a thickness can fully cope with the miniaturization of electronic components in recent years.

[0076] As the metal forming the metal foil, any appropriate metal can be used. For example, copper, aluminum, nickel, chromium, and gold can be mentioned. These can be used alone or in combination of two or more. The thickness of the metal foil is, for example, 2 μm to 35 μm.

[0077] As a method for preparing the above-mentioned laminate, any appropriate method can be adopted. For example, the above-mentioned resin composition is applied on the above-mentioned substrate to form a coating layer, and the above-mentioned metal foil is laminated on the coating layer to obtain a laminate. As another specific example, the above-mentioned resin composition is applied on the above-mentioned metal foil to form a coating layer to obtain a laminate. Typically, at any appropriate time point, the coating layer is subjected to energy imparting treatment such as heating or light irradiation to cure the coating layer. When applying, the above-mentioned resin composition can be dissolved in any appropriate solvent for use. Example

[0078] The present invention is specifically described below by way of examples, but the present invention is not limited to these examples. It is to be noted that, unless otherwise specified, the measuring methods of the various properties are as follows. In addition, unless otherwise specified, "%" and "ppm" are weight references. 1. The long diameter of the particle The major diameter of the particles was calculated by FE-SEM (field emission-scanning electron microscope) observation. Specifically, the major diameters of 100 primary particles randomly selected from the SEM photos of the particles were measured, and the arithmetic mean (average major diameter) of the obtained measured values ​​was obtained. It should be noted that the magnification of SEM observation was set to 10,000 times. 2. The short diameter of the particle The minor diameter of the particles was calculated by FE-SEM observation. Specifically, the minor diameters of 100 primary particles randomly selected from the SEM photograph of the particles were measured, and the arithmetic mean (average minor diameter) of the obtained measured values ​​was obtained. It should be noted that the magnification of SEM observation was set to 10,000 times. 3.D SL and D ST Through FE-SEM observation, D SL and D ST Specifically, the major diameters of 100 primary particles randomly selected from the SEM photograph of the particles were measured, and the value of the 75th particle (D 75L ) divided by the 25th value (D 25L ) and calculate D SL In addition, the short diameters of 100 primary particles randomly selected from the SEM photograph of the particles were measured, and the value of the 75th particle (D 75T ) divided by the 25th value (D 25T ) and calculate D ST . 4. Aspect Ratio The aspect ratio was calculated by FE-SEM observation. Specifically, the aspect ratio was calculated by dividing the average major axis of the particles by the average minor axis of the particles.

[0079] [Example 1] (Preparation of Hollow Silica Particles) The elliptical alunite particle powder (NaAl3(SO4)2(OH)6, long diameter: 1.98μm, D SL : 1.13, short diameter: 1.35μm, D ST : 1.18, aspect ratio: 1.47) 800 g was suspended in 5 L of ion exchange water to obtain a slurry of alunite particles.

[0080] Next, the obtained slurry of alunite particles was heated to 90° C. while being stirred, and 816 ml of 0.55 mol / L No. 3 water glass (Na2O·2.97SiO2, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added thereto over a period of 4 hours. The slurry thus obtained was aged for 1 hour, and then dehydrated and washed with water to obtain a cake of the first core-shell particle precursor. Next, the cake of the first core-shell particle precursor was dried at 105° C. for 1 day to obtain a powder of core-shell particles.

[0081] Next, the powder of the first core-shell particle precursor was suspended in 5L of ion exchange water, heated to 90°C while stirring, and 136ml of 0.55mol / L No. 3 water glass was added thereto over a period of 10 minutes. Then, 680mL of 0.55mol / L No. 3 water glass and 757ml of 0.50mol / L sulfuric acid were added simultaneously. Here, No. 3 water glass was added over a period of 50 minutes, and sulfuric acid was added over a period of 60 minutes. The slurry thus obtained was aged for 30 minutes, then dehydrated and washed with water to obtain agglomerates of the second core-shell particle precursor.

[0082] The obtained agglomerates of the second core-shell particle precursor were suspended in 5L of ion exchange water, heated to 90°C while stirring, and 136ml of 0.55mol / L No. 3 water glass was added thereto over a period of 10 minutes. Then, 680mL of 0.55mol / L No. 3 water glass and 757ml of 0.50mol / L sulfuric acid were added simultaneously. Here, No. 3 water glass was added over a period of 50 minutes, and sulfuric acid was added over a period of 60 minutes. The slurry thus obtained was aged for 30 minutes, then dehydrated, washed with water, and then dried at 105°C for 1 day to obtain a powder of core-shell particles.

[0083] Next, the obtained core-shell particle powder was calcined at 500° C. for 3 hours and further calcined at 550° C. for 1 hour. It is considered that the alunite particles change as follows by calcination. NaAl3(SO4)2(OH)6→NaAl(SO4)2+Al2O3+3H2O

[0084] Next, 6 L of ion exchange water was added to 737 g of the calcined core-shell particles, and the mixture was resuspended under stirring at room temperature. 3.95 L of 2 mol / L sulfuric acid was added thereto, and the mixture was heated to 90° C. and reacted for 5 hours to dissolve the core particles, thereby obtaining a slurry of the first hollow silica precursor. The first hollow silica precursor is also a hollow particle precursor. The obtained slurry of the first hollow silica precursor was dehydrated and washed with water to obtain agglomerates of the first hollow silica precursor.

[0085] Next, the obtained mass of the first hollow silica precursor (the amount of 88g of powder) was suspended with 4L of ion exchange water, heated to 90°C while stirring, and 40ml of No. 3 water glass of 0.55mol / L was added thereto for 10 minutes, and then 200mL of No. 3 water glass of 0.55mol / L and 210ml of sulfuric acid of 0.5mol / L were added at the same time. Here, No. 3 water glass was added for 50 minutes, and sulfuric acid was added for 60 minutes. The slurry thus obtained was aged for 30 minutes, then dehydrated and washed with water to obtain the mass of the second hollow silica precursor. Next, the obtained mass of the second hollow silica precursor was suspended in 4L of ion exchange water, heated to 90°C while stirring, and 40ml of No. 3 water glass of 0.55mol / L was added thereto over a period of 10 minutes, and then 200ml of No. 3 water glass of 0.55mol / L and 210ml of sulfuric acid of 0.50mol / L were added at the same time. Here, No. 3 water glass was added over a period of 50 minutes, and sulfuric acid was added over a period of 60 minutes. The slurry thus obtained was aged for 30 minutes, and then dehydrated and washed with water to obtain a mass of the third hollow silica precursor. Furthermore, the mass of the third hollow silica precursor obtained was suspended in 4L of ion exchange water, heated to 90°C while stirring, and 40ml of No. 3 water glass of 0.55mol / L was added thereto over a period of 10 minutes, and then 200ml of No. 3 water glass of 0.55mol / L and 210ml of sulfuric acid of 0.50mol / L were added at the same time. Here, No. 3 water glass was added over 50 minutes, and sulfuric acid was added over 60 minutes. The slurry thus obtained was aged for 30 minutes, and then dehydrated and washed with water to obtain agglomerates of the fourth hollow silica precursor.

[0086] Next, 2L of ion exchange water and 1083ml of 2mol / L sulfuric acid were added to the obtained agglomerates of the fourth hollow silica precursor (amount of 282g of powder), and the mixture was placed at 90°C for 1.5 hours to obtain a slurry of the fifth hollow silica precursor. The agglomerates were then dehydrated and washed with water, and dried at 105°C for 1 day to obtain powder of the fifth hollow silica precursor.

[0087] Next, the obtained fifth hollow silica precursor powder was calcined in an electric furnace at 800° C. for 1 hour and 1100° C. for 1 hour to obtain hollow silica particles. Specifically, the fifth hollow silica precursor powder was calcined in an air atmosphere to obtain hollow particles.

[0088] (Preparation of resin composition) 95.2 phr of bisphenol F epoxy resin ("JER806" manufactured by Mitsubishi Chemical Corporation) and 40 phr of the obtained hollow silica particles were mixed for 3 minutes using an autorotation-revolution mixer ("ARV-310P" manufactured by Thinky Corporation) at atmospheric pressure, at a rotation of 1000 rpm and a revolution of 2000 rpm to obtain a mixture. Hereinafter, the hollow silica particles may be referred to as fillers. The obtained mixture and 4.8 phr of an imidazole epoxy resin curing agent ("2E4MZ" manufactured by Shikoku Chemicals Co., Ltd.) were mixed for 3 minutes using an autorotation-revolution mixer at 1000 rpm, 2000 rpm, and 0.7 kPa to obtain a resin composition.

[0089] (Production of resin molded body) The obtained resin composition was poured into a Teflon (registered trademark) mold having a thickness of 1.0 mm and press-molded at 80° C. for 1 hour. After cooling, the molded body was taken out from the mold and placed in a dryer at 150° C. for 4 hours to further heat cure. Then, the molded body was cooled to obtain a sample for evaluation.

[0090] [Example 2] (Preparation of Hollow Silica Particles) The elliptical alunite particle powder (NaAl3(SO4)2(OH)6, long diameter: 1.98μm, D SL : 1.13, short diameter: 1.35μm, D ST : 1.18, aspect ratio: 1.47) 200 g was suspended in 1.4 L of ion exchange water to obtain a slurry of alunite particles.

[0091] Next, the obtained slurry of alunite particles was heated to 90° C. while being stirred, and 202 ml of 0.56 mol / L No. 3 water glass (Na2O·2.97SiO2, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added thereto over a period of 4 hours. The slurry thus obtained was aged for 1 hour, and then dehydrated and washed with water to obtain agglomerates of the first core-shell particle precursor. Next, the agglomerates of the first core-shell particle precursor were dried at 105° C. for 1 day to obtain a powder of core-shell particles.

[0092] Next, the powder of the first core-shell particle precursor was suspended in 1.4 L of ion exchange water, heated to 90 ° C while stirring, and 34 ml of 0.56 mol / L No. 3 water glass was added thereto over a period of 10 minutes. Then, 168 mL of 0.56 mol / L No. 3 water glass and 188 ml of 0.51 mol / L sulfuric acid were added at the same time. Here, No. 3 water glass was added over a period of 50 minutes, and sulfuric acid was added over a period of 60 minutes. The slurry thus obtained was aged for 30 minutes, then dehydrated and washed with water to obtain agglomerates of the second core-shell particle precursor.

[0093] The obtained agglomerates of the second core-shell particle precursor were suspended in 1.4 L of ion exchange water, heated to 90°C while stirring, and 34 ml of 0.56 mol / L No. 3 water glass was added thereto over a period of 10 minutes. Then, 168 mL of 0.56 mol / L No. 3 water glass and 188 ml of 0.51 mol / L sulfuric acid were added simultaneously. Here, No. 3 water glass was added over a period of 50 minutes, and sulfuric acid was added over a period of 60 minutes. The slurry thus obtained was aged for 30 minutes, then dehydrated and washed with water, and then dried at 105°C for 1 day to obtain a powder of core-shell particles.

[0094] Next, the obtained core-shell particle powder was calcined at 500° C. for 3 hours and further calcined at 550° C. for 1 hour. It is considered that the alunite particles change as follows by calcination. NaAl3(SO4)2(OH)6→NaAl(SO4)2+Al2O3+3H2O

[0095] Next, 1305 ml of ion exchange water was added to 177 g of the calcined core-shell particles, and the particles were resuspended under stirring at room temperature. 555 ml of 3.35 mol / L sulfuric acid was added thereto, and the mixture was heated to 90° C. and reacted for 5 hours to dissolve the core particles, thereby obtaining a slurry of the first hollow silica precursor. The obtained slurry of the first hollow silica precursor was dehydrated and washed with water to obtain agglomerates of the first hollow silica precursor.

[0096] Next, the obtained mass of the first hollow silica precursor (the amount of 18.8g of powder) was suspended with 1.36L of ion exchange water, heated to 90°C while stirring, and 20ml of No. 3 water glass of 0.56mol / L was added thereto over a period of 10 minutes, and then 100mL of No. 3 water glass of 0.56mol / L and 105ml of sulfuric acid of 0.51mol / L were added at the same time. Here, No. 3 water glass was added over a period of 50 minutes, and sulfuric acid was added over a period of 60 minutes. The slurry thus obtained was aged for 30 minutes, then dehydrated and washed with water to obtain a mass of the second hollow silica precursor. Next, the obtained mass of the second hollow silica precursor was suspended with 1.36L of ion exchange water, heated to 90°C while stirring, and 20ml of No. 3 water glass of 0.56mol / L was added thereto over a period of 10 minutes, and then 100mL of No. 3 water glass of 0.56mol / L and 105ml of sulfuric acid of 0.51mol / L were added at the same time. Here, No. 3 water glass was added over a period of 50 minutes, and sulfuric acid was added over a period of 60 minutes. The slurry thus obtained was aged for 30 minutes, then dehydrated and washed with water to obtain a mass of the third hollow silica precursor. Furthermore, the obtained mass of the third hollow silica precursor was suspended with 1.36L of ion exchange water, heated to 90°C while stirring, and 20ml of No. 3 water glass of 0.56mol / L was added thereto over a period of 10 minutes, and then 100mL of No. 3 water glass of 0.56mol / L and 105ml of sulfuric acid of 0.51mol / L were added at the same time. Here, No. 3 water glass was added over a period of 50 minutes, and sulfuric acid was added over a period of 60 minutes. The slurry thus obtained was aged for 30 minutes, then dehydrated and washed with water to obtain the mass of the fourth hollow silica precursor.

[0097] Next, 1.36 L of ion exchange water and 146 ml of 3.35 mol / L sulfuric acid were added to the obtained agglomerates of the fourth hollow silica precursor (amount of 52.8 g of powder), and the mixture was placed at 90° C. for 1.5 hours to obtain a slurry of the fifth hollow silica precursor. The agglomerates were then dehydrated and washed with water, and dried at 105° C. for 1 day to obtain powder of the fifth hollow silica precursor.

[0098] Next, the obtained powder of the fifth hollow silica precursor was calcined at 800° C. for 1 hour and at 1100° C. for 1 hour in an electric furnace (under air atmosphere) to obtain hollow silica particles.

[0099] (Production of resin molded body) A molded body (evaluation sample) was obtained in the same manner as in Example 1 except that the hollow silica particles were used.

[0100] [Example 3] (Preparation of Hollow Silica Particles) The elliptical alunite particle powder (NaAl3(SO4)2(OH)6, long diameter: 1.98μm, D SL : 1.13, short diameter: 1.35μm, D ST : 1.18, aspect ratio: 1.47) 1500 g was suspended in 7.5 L of ion exchange water to obtain a slurry of alunite particles.

[0101] Next, the obtained slurry of alunite particles was heated to 90° C. while being stirred, and 1507 ml of 0.54 mol / L No. 3 water glass (Na2O·3.14SiO2, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added thereto over a period of 4 hours. The obtained slurry was aged for 1 hour, then dehydrated and washed with water to obtain agglomerates of the first core-shell particle precursor.

[0102] Next, the obtained agglomerates of the first core-shell particle precursor were suspended in 7.5 L of ion-exchanged water, heated to 90° C. while stirring, and 1507 ml of 0.54 mol / L No. 3 water glass was added thereto over a period of 2 hours. The slurry thus obtained was aged for 1 hour, left under stirring for 15 hours, then dehydrated and washed with water to obtain agglomerates of the second core-shell particle precursor. The obtained agglomerates of the second core-shell particle precursor were suspended in 7.5 L of ion-exchanged water, heated to 90° C. while stirring, and 1507 ml of 0.54 mol / L No. 3 water glass was added thereto over a period of 2 hours. The obtained slurry was aged for 1 hour, left under stirring for 15 hours, then dehydrated and washed with water, and then dried at 100° C. for 1 day to obtain a powder of core-shell particles.

[0103] Next, the obtained core-shell particle powder was calcined at 500° C. for 3 hours and further calcined at 550° C. for 1 hour. It is considered that the alunite particles change as follows by calcination. NaAl3(SO4)2(OH)6→NaAl(SO4)2+Al2O3+3H2O

[0104] Next, 6 L of ion exchange water was added to 864 g of the calcined core-shell particles, and the particles were resuspended under stirring at room temperature. 7.8 L of 1 mol / L sulfuric acid was added thereto, and the mixture was heated to 90° C. and reacted for 5 hours to dissolve the core particles, thereby obtaining a slurry of the first hollow silica precursor. The obtained slurry of the first hollow silica precursor was dehydrated and washed with water to obtain agglomerates of the first hollow silica precursor.

[0105] Next, the obtained mass of the first hollow silica precursor (the amount of 130g of powder) was suspended with 860ml of ion exchange water, heated to 90°C while stirring, and 33ml of No. 3 water glass of 0.54mol / L was added thereto for 10 minutes, and then 163mL of No. 3 water glass of 0.54mol / L and 186ml of sulfuric acid of 0.50mol / L were added at the same time, No. 3 water glass was added for 50 minutes, and sulfuric acid was added for 60 minutes. The slurry thus obtained was aged for 30 minutes, then dehydrated and washed with water to obtain a mass of the hollow silica precursor. Then the same operation was repeated twice to obtain a mass of the second hollow silica precursor.

[0106] Next, 2L of ion exchange water and 400ml of 2.87mol / L sulfuric acid were added to the obtained agglomerates of the second hollow silica precursor (amount of 284g of powder), and the mixture was placed at 90°C for 1.5 hours to obtain a slurry of the third hollow silica precursor. The agglomerates were then dehydrated and washed with water, and dried at 100°C for 1 day to obtain powder of the third hollow silica precursor.

[0107] Next, the obtained powder of the third hollow silica precursor was calcined at 800° C. for 1 hour and at 1100° C. for 1 hour in an electric furnace (under air atmosphere) to obtain hollow silica particles.

[0108] (Production of resin molded body) A molded body (evaluation sample) was obtained in the same manner as in Example 1 except that the hollow silica particles were used and the amount of the hollow silica particles was 25 phr. It should be noted that an attempt was made to blend the hollow silica particles in the same amount as in Example 1, but no further blending was possible.

[0109] [Comparative Example 1] A molded body (evaluation sample) was obtained in the same manner as in Example 1 except that the hollow silica particles were not blended.

[0110] <XRD measurement> The hollow silica particles of Examples 1, 2, and 3 were analyzed by X-ray diffraction ("EMPYRIAN" manufactured by PANalytical Corporation), and the results showed that the hollow silica particles were amorphous silica.

[0111] <TEM-EDS measurement> For the hollow silica particles of Examples 1, 2 and 3, images were acquired using a transmission electron microscope ("JEM-2100PLUS" manufactured by JEOL Ltd.) and an attached energy dispersive X-ray spectrometer (JED2300 series manufactured by JEOL Ltd.) at an accelerating voltage of 200 kV and a magnification of 200,000 times, and composition analysis was performed at three points in the thickness direction in point analysis mode. The observation results of the hollow silica particles of Example 1 are shown in Figure 5A The observation results of the hollow silica particles of Example 2 are shown in Figure 5B The observation results of the hollow silica particles of Example 3 are shown in Figure 5C In addition, the atomic ratios of oxygen (O), aluminum (Al), and silicon (Si) obtained from the obtained peak intensities are also shown. In all of them, a tendency that the amount of Al decreases from the inside to the outside of the shell is confirmed.

[0112] The following evaluations were also performed on the hollow silica particles of Examples 1, 2, and 3. The evaluation results are summarized in Table 1. 1.Al content The Al content is determined by pretreatment, and an Al content determination sample is prepared from hollow silica particles, and analyzed by high-frequency inductively coupled plasma atomic emission spectrometry (ICP-AES). Specifically, 250 mg of hollow silica particles are measured and put into a beaker made of PMP (polymethylpentene) resin. Then, the hollow silica particles are fused with ultrapure water, and then 3 ml of nitric acid and 5 ml of hydrofluoric acid are added to heat and dissolve. After concentrating to 5 ml, a 1% aqueous solution of boric acid is added to mask the residual hydrofluoric acid, deactivate it and heat for 10 minutes to avoid damage to the analytical instrument. After cooling, dilute to 50 ml with ultrapure water to prepare an Al content determination sample for analysis. From the obtained results, the Al content ratio was calculated. 2.Na content The Na content is determined by pretreatment, and a Na content determination sample is prepared from hollow silica particles, and analyzed by atomic absorption spectroscopy (AAS). Specifically, 250 mg of hollow silica particles are measured and put into a beaker made of PMP (polymethylpentene) resin. Then, the hollow silica particles are fused with ultrapure water, and then 3 ml of nitric acid and 5 ml of hydrofluoric acid are added to heat and dissolve. After concentrating to 5 ml, a 1% boric acid aqueous solution is added to mask the residual hydrofluoric acid, deactivate it and heat for 10 minutes to avoid damage to the analytical instrument. After cooling, dilute to 50 ml with ultrapure water to prepare a Na content determination sample for analysis. From the obtained results, the content ratio of Na was calculated. 3. The thickness of the shell of the hollow particle By TEM observation, the thickness of the shell of the particle is calculated. Specifically, the thickness of the shell of 10 primary particles randomly selected from the TEM photo of the particle is measured, and the arithmetic mean (average thickness) of the measured value obtained is obtained. It should be noted that the magnification of TEM observation is set to 10000 times and 100000 times. 4. Hollowness The hollowness is calculated from the major and minor diameters and the shell thickness. Specifically, the shape of the particle is approximated to the volume of a cylinder using the primary particle diameter (major diameter, minor diameter) and the shell thickness, and the hollowness is calculated using the following formula. Hollowness ratio = hollow area volume of hollow particles ÷ volume of hollow particles × 100 Volume of hollow particle = π × radius 2 × height = π × (longest diameter ÷ 2) 2 × Short diameter The hollow area volume of hollow particles = π×((longest diameter - shell thickness×2)÷2)2 ×(minor diameter - shell thickness × 2) 5.BET specific surface area The specific surface area was measured by "BELsorp-mini" manufactured by Microtrac BEL Co., Ltd. Specifically, the specific surface area was determined by measuring by a constant volumetric gas adsorption method using nitrogen gas and analyzing by a BET multipoint method. 6. Micropore volume The micropore volume was measured by "BELsorp-max" manufactured by Microtrac BEL Co., Ltd. Specifically, the micropore volume (the cumulative micropore volume of micropores with a diameter of 1 nm to 100 nm and the cumulative micropore volume of micropores with a diameter of 1 nm to 10 nm) was obtained by measuring the micropore volume by constant volume gas adsorption method using nitrogen and analyzing the micropore volume by BJH (Barrett-Joyner-Halenda) method. 7. Density The density was determined by nitrogen replacement. Specifically, a gas replacement density measuring device (Micromeritics, dry automatic density meter AccuPyc II 1340) was used to collect 0.15 to 0.2 g of sample at 1 cm 3 The measurement was performed in a sample cell with nitrogen. The measurement was repeated 5 times or more and the average value was calculated. 8. Dielectric constant and dielectric loss tangent The dielectric constant and dielectric loss tangent were measured by the cavity resonance method using a dielectric constant measuring device for powders. The measurement was performed at 10 GHz under the conditions of a temperature of 25°C and a humidity of 44% RH. It should be noted that the density required for calculating the dielectric properties was the density value obtained by the above-mentioned nitrogen replacement method. 9. Oil absorption To 1 g of the hollow silica particles to be measured, epoxy resin ("JER819" manufactured by Mitsubishi Chemical Corporation) is added dropwise and mixed, and the oil absorption is calculated from the amount of epoxy resin added when the slurry is formed according to the following conversion formula. Specifically, the epoxy resin is repeatedly added dropwise and mixed to the hollow silica particles, and the point at which the hollow silica particles become a slurry is defined as the end point. The addition near the end point is performed while the epoxy resin is allowed to fuse drop by drop. Then, the amount of epoxy resin per 1 g of the measured object is calculated using the following formula, and the obtained oil absorption per 1 g of the measured object is divided by the specific surface area of ​​the measured object to calculate the surface area per unit area (m2). 2 ) of oil absorption. Oil absorption per 1g of the measurement object (particles) = epoxy resin titration (g) / mass of the powder of the measurement object (g) Surface area per unit area (m 2) = oil absorption per 1g of the measured object (particles) (g / g) / specific surface area of ​​the powder of the measured object (m 2 / g)

[0113] <Evaluation of resin molded article> The resin molded bodies (evaluation samples) of the examples and comparative examples were subjected to density measurement, cross-sectional observation, and dielectric property measurement. In addition, the void ratio of the resin molded body, the filler density in the resin molded body, and the filler hollow ratio in the resin molded body were calculated. The evaluation results are summarized in Table 1. The results of observing the resin molded body of Example 1 at 2000 times are shown in Table 1. Figure 6 .

[0114] (Determination of density) The density of the resin molded body was measured using an electronic density meter ("SD120L" manufactured by ALFA MIRAGE Co., Ltd.) Specifically, the obtained resin molded body was cut into a size of 5 cm×6 cm using an ultrasonic cutter, and the cut molded body sample was used for measurement.

[0115] 1. Porosity of resin molded body From the above density measurement results, the void ratio (ratio of the volume of air in the resin molded body) Va% of the resin molded body is calculated. 2. Filler density in resin molded body The filler density in the resin molded body is calculated by the following formula. The filler density in the resin molded body is calculated by subtracting the volume of the resin component from the volume of the resin molded body containing the filler, and dividing the filler addition by the calculated filler volume. The volume of the resin molded body containing the filler is measured by an electronic density meter ("SD120L" manufactured by ALFA MIRAGE). The volume of the resin component is separately calculated by the weight and density of a blank resin molded body made without the filler. Filler density in resin molded body = wf / (Vc-mr / ρr) = wf / (Vc-100 / ρr) wf: weight of particles (filler) when the weight of the resin is 100 parts by weight (phr) Vc: Volume of resin molded body mr: weight of resin (g) ρr: Density of resin (g / ml) 3. Filler hollow ratio in resin molded body From the value of the void ratio Va% of the resin molded body, the filler void ratio Va / (Va+Vs) in the resin molded body is calculated. Here, Vs can be obtained by the following formula. [Number 1] Vc: Volume of resin molded body Vs: Volume of the particle's shell Va: Volume of air in the resin molded body Vr: Volume of resin mc: Weight of resin molded body (g) ρc: Density of resin molded body (g / ml) ms: particle (shell) weight (g) ρs: density of the particle shell (2.28 (g / ml)) mr: weight of resin (g) ρr: Density of resin (g / ml) wf: weight parts (phr) of particles (filler) when the weight of the resin is 100 parts by weight (phr)

[0116] (Cross-sectional observation of resin molded body) The obtained molded body sample was cut using a cross-section polisher ("IB-09010CP" manufactured by JEOL Ltd.), and the cross section was observed using a FE-SEM ("JSM-7600F" manufactured by JEOL Ltd., magnification: 2000x, 5000x, or 10000x).

[0117] (Determination of dielectric constant and dielectric loss tangent) The dielectric constant and dielectric loss tangent of the obtained molded product sample were measured under the following conditions. ■Measurement method: Based on IEC 62810 (cavity resonator perturbation method) ■ Sample shape: Length 55mm or more, width 1.6-2.4mm, height 0.7-1.0mm ■Test conditions: Frequency 10 GHz ■Number of measurements: 2 times ■ Conditioning: 23℃±1℃, 50%RH±5%RH, 24 hours < ■Laboratory environment: 23℃±1℃, 50%RH±5%RH ■Measurement device: PNA network analyzer N5222B (manufactured by Keysight Technologies) ■ Cavity resonator: CP531 for 10 GHz (manufactured by Kanto Denshi Application Development Co., Ltd.)

[0118] [Table 1]

[0119] In various embodiments, Figure 6As shown, by observing the cross section of the resin molded body, it was confirmed that the resin did not penetrate into the hollow region, thereby confirming that the destruction of the hollow particles was suppressed. From Examples 1 and 2 with low oil absorption, it can be seen that more fillers can be added to the resin, so that the dielectric properties of the resin composition (resin molded body) are more excellent. Industrial Applicability

[0120] The hollow particles of the present invention are typically applicable to electronic materials, and can also be used in, for example, heat insulating materials, sound insulating materials, impact buffering materials, stress buffering materials, optical materials, and lightweight materials.

[0121] Description of Reference Numerals L: long diameter T: short diameter 2: Hollow particles 4: Shell 6: Space (hollow part) 10: Laminated body 11: Resin layer 12: Metal foil

Claims

1. A hollow particle having a shell with a hollow interior, characterized in that: The shell is silicon dioxide containing aluminum, and the amount of the aluminum present in the first portion is greater than that in the second portion, the first portion is located on the inner side of the shell in the thickness direction of the shell, and the second portion is located on the outer side of the shell in the thickness direction of the shell compared to the first portion.

2. The hollow particles according to claim 1, wherein The aluminum content is less than 1% of the components constituting the shell.

3. The hollow particles according to claim 1, wherein The amount of the aluminum decreases from the inside to the outside of the shell.

4. The hollow particles according to claim 1, wherein The oil absorption of epoxy resin is less than 0.6g / m 2 .

5. The hollow particles according to claim 1, wherein The shell further contains sodium, and the sodium content of the shell is 3000 ppm or less.

6. The hollow particles according to claim 1, wherein The silicon dioxide mentioned above is amorphous silicon dioxide.

7. The hollow particles according to claim 1, wherein The shell has a hollow ratio of 30% to 95%.

8. The hollow particles according to claim 1, wherein The shell has a thickness of 25 nm to 500 nm.

9. The method for producing hollow particles according to any one of claims 1 to 8, comprising the following steps: The core particles are covered with a shell-forming material to obtain core-shell particles. removing the core particles from the core-shell particles to obtain a hollow particle precursor, and The hollow particle precursor is coated with a shell-forming material.

10. The manufacturing method according to claim 9, wherein: The core particles contain an alunite-type compound represented by the following general formula (I): M a [Al 1-x M' x ]3(SO4 2- ) y (OH) z ·mH2O……(I) In formula (I), M is selected from Na + , K + NH4 + and H3O + At least one cation in the formula, M' is selected from Cu 2+ 、Zn 2+ 、Ni 2+ Sn 4+ 、Zr 4+ and Ti 4+ At least one cation in the mixture, a satisfies 0.8≤a≤1.35, m satisfies 0≤m≤5, x satisfies 0≤x≤0.4, y satisfies 1.7≤y≤2.5, and z satisfies 4≤z≤7.

Citation Information

Patent Citations

  • Hollow particle, resin composition, and resin molded article and laminate each using said resin composition

    WO2021171858A1

  • Hollow particles, method for producing said hollow particles, resin composition, and resin molded article and laminate using said resin composition

    WO2021171859A1